Potassium channel subfamily T member 1(KCNT1) pathological variant causing epilepsy of infancy with migrating focal seizures: a case report - Prem Chand; Meher Angez; Ayesha Nasir Hameed; Salman Kirmani (Journal of the Pakistan Medical Association, 2023)
Pathological mutation of potassium channel subfamily T member 1 (KCNT1) gene causes an autosomal dominant disorder characterised by secondarily generalised seizures/migratory focal seizure, cyanosis, and dysmorphic features. We report the case of a five-month-old male with pathological KCNT1 variant who presented with focal clonic seizures, Mongol spots, and grade two systolic murmur at the left lower sternal border and loud P2. The seizures were refractory to most anti-epileptic drugs but showed some response to Valproic acid. This case demonstrated that EIMFS is a grave infantile epileptic encephalopathy which is refractory to anti-epileptic drugs and can present with a wide spectrum of neurogenic and cardiogenic symptoms. Keywords: KCNT1; Mutation; Paediatric; Pakistan.